FEM Analysis of Textile Reinforced Composite Materials Impact Behavior - Ionesi, Savin Dorin; Ciobanu, Luminita; Dumitras, Catalin; Avadanei, Manuela; Dulgheriu, Ionut; Ionescu, Irina; Loghin, Maria Carmen (Materials, 2021)
Composite materials reinforced with textile fabrics represent a complex subject. When explaining these materials, one must consider their mechanical behavior in general, and impact resistance in particular, as many applications are characterized by dynamic strains. Impact characteristics must be considered from the early stages of the design process in order to be controlled through structure, layer deposition and direction. Reinforcement materials are essential for the quality and behavior of composites, and textile reinforcements present a large range of advantages. It takes a good understanding of the requirements specific to an application to accurately design textile reinforcements. Currently, simulations of textile reinforcements and composites are efficient tools to forecast their behavior during both processing and use. The paper presents the steps that must be followed for modelling the impact behavior of composite materials, using finite element analysis (FEM). The FEM model built using Deform 3D software offers information concerning the behavior structure during impact. The behavior can be visualized for the structure as a whole and, for different sections, be considered significant. Furthermore, the structure’s strain can be visualized at any moment. In real impact tests, this is not possible due to the very short time interval and the impossibility to record inside the structure, as well as to record all significant stages using conventional means.